Application of Science, Technology, and Digital Transformation in Preserving, Promoting Cultural Values and Building a Culturally Distinct Quảng Ninh - Thanh Tam, Ho; Van Kim, Nguyen (VNU Journal of Science: Policy and Management Studies, 2026)
Abstract: The Fourth Industrial Revolution has been creating profound and transformative changes in human life. Societies are redefining themselves, restructing governance institutions, establishing new regulatory mechanisms within the digital space. In many respects, this new industrial revolution is not merely about technological advancement; it also represents a fundamental development in productive capacity and human creativity, grounded in science, technology, and innovation, marking a transition to a new stage and level of development. In this article, we focus on analyzing the role of science, technology, and digital transformation in preserving and promoting cultural values in Vietnam (through a case study of Quang Ninh). At the same time, we propose several solutions for building a culturally rich and distinctive Quang Ninh today. This is not only an objective requirement to meet new development goals but also a demonstration of statregic self-reliance thinking, enable Quang Ninh to maintain high growth rates and sustains its pioneering position in shaping development models in the new era.   Keywords: Science and technology, digital transformation, cultural preservation, building cultural identity, Quang Ninh people.